The Impact of Educational Institutions on the Care and Rehabilitation of Children and Individuals with High Determination, and Their Integration into Society - Al-Humaid, Prof. Dr. Barzan Muyassar Hamed Al-Humaid (Sulaimani Journal for Humanities, 2026)
Numerous studies indicate that the problems of life and compatibility with disabilities are not due to injury or disability per se, but mainly to the way society views them. The basic question is: What are the roles that society, with all its systems and institutions, can play to provide people with special needs with knowledge, attitudes, values, and skills that enable them to participate in such participation and be accepted by society? This question and other sub-questions are answered through the results of the study, which we will reveal in the course of the research. The importance of the study comes through the adoption of a strategy by the various educational and educational institutions that works on preparing and rehabilitating this special category and integrating them within their societies and benefiting from their potentials, whatever they may be. From the foregoing, we will discuss in this modest study the role that educational and educational institutions, as well as civil society organizations, can play in preparing and rehabilitating people with special needs and giving them rights that guarantee them a decent human life and enable them to integrate into society and benefit from their potential and capabilities, whatever they may be. The study plan included an introduction, three sections and a conclusion. In the introduction, we detailed the reason for choosing the topic, its importance, objectives, and study plan. As for the first topic, it came in the statement of the concept of disability according to the Islamic and social perception, while the second topic dealt with identifying the pros and cons in the light of social integration, and the third topic And the last one was devoted to talking about the role of educational and educational governmental institutions in achieving the requirements and rehabilitation of people with special needs, to get to the conclusion in which we wrote the most important results and recommendations.
Keywords: institutions; educational; rehabilitation; needs; special